Renal Denervation is Promising as a Treatment for Resistant Hypertension - Nichols, Emma Hitt (MD Conference Express, 2013)
The sympathetic nervous system (SNS) has recently been hypothesized to play a key role in resistant hypertension. As a result, recent studies have explored renal artery denervation therapy as a potential treatment option for patients with resistant hypertension. This article discusses the current and future landscape of renal denervation therapy, as well as potential mechanisms by which increased sympathetic activity may result in effect blood pressure.